The Effectiveness of the Fun Easy Learn Application in Improving Arabic Vocabulary Mastery - Ratu Zahara Juwita; Wahab Wahab; Irfan Irfan; Budi Sanjaya; Erma Suryani; Mohamad Hussin (Ijaz Arabi Journal of Arabic Learning, 2026)
The purpose of this research was to analyze the efficacy of the Fun Easy Learn app in enhancing seventh-graders' command of the Arabic lexicon (mufradat). The study used a one-group pretest-posttest design, which is a quasi-experimental approach. There were 27 participants, drawn at random from a pool of 100 pupils. Vocabulary tests were given both before and after the therapy to gather data. The three topics addressed by the instruments were animals, jobs, and body parts. The data were analyzed using descriptive and inferential statistics in SPSS version 31.0. This included tests for normality and homogeneity, as well as one-way ANOVA and paired-samples t-tests for hypothesis testing. After using the Fun Easy Learn app, pupils' vocabulary skills significantly improved, according to the findings. Scores improved from an average of 32.04 on the pretest to 67.78 on the posttest. At a significance threshold of 0.000 (p < 0.05), the paired-samples t-test yielded a t-value of -6.819, indicating a statistically significant difference between the pretest and posttest scores. Based on these results, it's clear that the Fun Easy Learn app helps students learn Arabic words faster. Students were more invested, enthusiastic, and motivated to study Arabic because of the app's interactive elements, including images, audio pronunciation, and educational activities. We may conclude that the Fun Easy Learn app is a useful tool for madrasah students to increase their Arabic vocabulary.